Becoming jelly: A call for gelatinous pedagogy within higher education - Bengtsen, Søren S. E.; Nørgård, Rikke T. (Proceedings of the International Conference on Networked Learning, 2014)
This paper calls for a debate concerning the dominant tropes, which we have assigned the power to define learning processes in higher education today. The argument of the paper takes a critical stand towards the tropes of taxonomy-based and Bildung-oriented understandings of learning processes and student voice in higher education. We argue that learning processes are more than mere phenomena of linear progression capable of being measured based on pre-set criteria for learning outcomes. On the other hand, we do not argue, that it is productive to take the easy way out using an abstract and shadowy vocabulary of Bildung, authenticity and personal growth. Instead we call for a new vocabulary in educational theory, which is capable of addressing the half-formed, premature and idiosyncratic dimensions of learning processes present in the everyday life of higher education. Inspired by the jelly as a metaphor, and drawing on thinkers such as Richard Sennett, Graham Harman and Friedrich Nietzsche, we call for a gelatinous pedagogy, which, in thought and language, match the motley-coloured, mongrel and queer developmental processes and strategies applied by students and teachers in higher education practice. By developing and applying the jelly as a new metaphor for learning processes and student voice in higher education we are able to address critical issues otherwise overlooked. Out of this application three findings and one suggestion for further research emerge: Firstly, vocabularies for understanding learning processes must have the ambition of making visible those queer processes. This must be done in a language and using a vocabulary, which has gelatinous qualities enabling the capability to grasp specific learning experiences in situ. Secondly, such a language should embrace the tentative, uncertain and troublesome character of learning processes – hereby acknowledging that such processes might never reach an end point and therefore not necessarily lead anywhere. Thirdly, an understanding of learning processes, therefore, cannot be adequately understood as a fixed structure or linear layout, but must rather be approached as jelly-like structures of entanglement and swarm. Fourthly, and finally, the challenge for understanding networked learning within higher education in a more nuanced way can be met by developing a gelatinous pedagogy; a pedagogy linguistically and conceptually sensitive to the multifarious dimensions of learning and being whether these be skills, forms of identity, or sheer ambivalence and obscurity in thought.